2019
DOI: 10.5433/1679-0359.2019v40n3p1115
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of water consumption estimates for tropical and winter forages by FDR probes and weighing lysimeters

Abstract: Soil moisture determination is essential for a good use of available water resources. In this regard, the use of frequency domain reflectometry (FDR) probes has as advantages mobility and practicality in relation to lysimeters. The experiment was carried out between April and June 2016 at the Luiz de Queiroz College of Agriculture (ESALQ/USP), located in Piracicaba, SP at the geographical coordinates 22°42?14.6? S and 47°37?24.1? W and altitude of 546 m. This study aimed to assess these FDR probes to estimate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…A previous study from [15] reported a high correlation between the height of the plant and the thermal time. The authors observed that growing degree-day accumulation was slightly lower in a cut cycle during autumn/winter with 12 days more than spring/summer cut cycles.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…A previous study from [15] reported a high correlation between the height of the plant and the thermal time. The authors observed that growing degree-day accumulation was slightly lower in a cut cycle during autumn/winter with 12 days more than spring/summer cut cycles.…”
Section: Introductionmentioning
confidence: 83%
“…In the Brazilian context, meat and leather became essential export goods around the end of century XVIII. Nowadays, the country is one of the main global players exporting to destinations like Russia and China [15].…”
Section: Introductionmentioning
confidence: 99%
“…Among them, monitoring SWC at a point scale (less than 0.01 cm 2 ) has advanced with various in-situ sensors, and the FDR method has been widely used [16]. The FDR method can measure the soil apparent dielectric constant using Water 2021, 13, 2712 2 of 8 the electromagnetic pulse principle, according to the frequency of the electromagnetic waves propagating in the soil [17][18][19][20]. Because soil dielectric content is related to the SWC, the dynamic SWC can be calculated using the relationship curve generated by the FDR method.…”
Section: Introductionmentioning
confidence: 99%